Circulating Levels of miR‐133a Predict the Regression Potential of Left Ventricular Hypertrophy After Valve Replacement Surgery in Patients With Aortic Stenosis. Issue 4 (15th August 2013) - García, Raquel; Villar, Ana V.; Cobo, Manuel; Llano, Miguel; Martín‐Durán, Rafael; Hurlé, María A.; Francisco Nistal, J.
Abstract : Background: Myocardial microRNA‐133a (miR‐133a) is directly related to reverse remodeling after pressure overload release in aortic stenosis patients. Herein, we assessed the significance of plasma miR‐133a as an accessible biomarker with prognostic value in predicting the reversibility potential of LV hypertrophy after aortic valve replacement (AVR) in these patients. Methods and Results: The expressions of miR‐133a and its targets were measured in LV biopsies from 74 aortic stenosis patients. Circulating miR‐133a was measured in peripheral and coronary sinus blood. LV mass reduction was determined echocardiographically. Myocardial and plasma levels of miR‐133a correlated directly ( r =0.46, P <0.001) supporting the myocardium as a relevant source of plasma miR‐133a. Accordingly, a significant gradient of miR‐133a was found between coronary and systemic venous blood. The preoperative plasma level of miR‐133a was higher in the patients who normalized LV mass 1 year after AVR than in those exhibiting residual hypertrophy. Logistic regression analysis identified plasma miR‐133a as a positive predictor of the hypertrophy reversibility after surgery. The discrimination of the model yielded an area under the receiver operator characteristic curve of 0.89 ( P <0.001). Multiple linear regression analysis revealed plasma miR‐133a and its myocardial target Wolf‐Hirschhorn syndrome candidate 2/Negative elongation factor A as opposite predictors of the LV mass loss (g) after AVR. Conclusions: Preoperative plasma levels of miR‐133a reflect their myocardial expression and predict the regression potential of LV hypertrophy after AVR. The value of this bedside information for the surgical timing, particularly in asymptomatic aortic stenosis patients, deserves confirmation in further clinical studies.